Neutrophil–Lymphocytes Ratio as Potential Early Marker for Alzheimer’s Disease - Carlo Cervellati; Dario Pedrini; Pietro Pirro; Paola Guindani; Carlo Renzini; Gloria Brombo; Giovanni Zuliani (Mediators of Inflammation)
Background. Neutrophil–lymphocyte ratio (NLR) is a noninvasive, inexpensive, and easily applicable marker of inflammation. Since immune dysregulation leading to inflammation is regarded as a hallmark of dementia, in particular Alzheimer’s disease (AD), we decided to investigate the potentials of NLR as a diagnostic and predictive biomarker in this clinical setting. Materials and Methods. NLR was measured in the blood of patients with AD (n = 103), amnestic type mild cognitive impairment (aMCI, n = 212), vascular dementia (VAD, n = 34), and cognitively healthy Controls (n = 61). One hundred twelve MCI patients underwent a regular clinical follow-up. Over a 36-months median follow-up, 80 remained stable, while 32 progressed to overt dementia. Results. NLR was higher in patients with aMCI or dementia compared to Controls; however, the difference was statistically significant only for aMCI (+13%, p=0.04) and AD (+20%, p=0.03). These results were confirmed by multivariate logistic analysis, which showed that high NLR was associated with an increase in the likelihood of receiving a diagnosis of aMCI (odd ratio (OR): 2.58, 95% confidence interval (CI): 1.36–4.89) or AD (OR: 3.13, 95%CI: 1.47–6.70), but not of VAD. NLR did not differ when comparing stable vs. progressing aMCI. Conclusions. This is the first report showing that NLR is significantly increased in MCI and AD but not in VAD. We also found that NLR was unable to predict the conversion from aMCI to AD. Further research on larger cohorts is warranted to definitely ascertain the application of NLR as a possible marker for aMCI and AD.